2020
DOI: 10.1088/1757-899x/805/1/012038
|View full text |Cite
|
Sign up to set email alerts
|

Ecofriendly production of silver nanoparticles from the seeds of Carica papaya and its larvicidal and antibacterial efficacy against some selected bacterial pathogens

Abstract: Carica papaya seed extract (CPE) was used in the synthesis of silver nanoparticles (AgNPs) in this study. For the characterization of biosynthesized particles, UV-vis spectroscopy, FTIR, FESEM and EDX were used. Antimicrobial and larvicidal efficacies of the synthesized AgNPs were assessed in the fight against certain pathogens and the Aedes aegypti 4th instar larvae. The absorption spectrum of AgNPs peaked at 433 nm with a broad peak of 3000 to 3800 cm−1 for different functional groups as presented in the FTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
2
3
0
Order By: Relevance
“…For the confirmation of the synthesis and characterization of silver nanoparticles, the SPR bands (420-435 nm) were recorded in this report in experiments conducted with the callus, peel, bark, juice, seed, and bark extracts of Carica papaya. These findings are in close agreement with the work reported by Aina et al [19], Balavijayalakshmi and Ramalakshmi [14], Mortazavi-Derazkola et al [20], Pandit [21], and Zia and Chaudhary [22]. John et al [23] comprehensively discussed the preparation of Carica papaya peel extract to synthesize the silver nanoparticles.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For the confirmation of the synthesis and characterization of silver nanoparticles, the SPR bands (420-435 nm) were recorded in this report in experiments conducted with the callus, peel, bark, juice, seed, and bark extracts of Carica papaya. These findings are in close agreement with the work reported by Aina et al [19], Balavijayalakshmi and Ramalakshmi [14], Mortazavi-Derazkola et al [20], Pandit [21], and Zia and Chaudhary [22]. John et al [23] comprehensively discussed the preparation of Carica papaya peel extract to synthesize the silver nanoparticles.…”
Section: Discussionsupporting
confidence: 89%
“…John et al [23] comprehensively discussed the preparation of Carica papaya peel extract to synthesize the silver nanoparticles. They found the SPR band at 420-445 nm, a rod-like morphology, 70-95 nm-size particles, and the pure crystalline nature of silver through UV-Vis, SEM, TEM, and XRD, respectively [19]. The findings of Parsad et al are different from the reported work as they have obtained UV-Vis Spectra at 402 nm in their report on the synthesis of AgNPs from leaf extracts of the G. glauca plant [24].…”
Section: Discussionmentioning
confidence: 81%
“…The peak value at 1594.36 cm −1 (in VPPE) which was shifted to 1634.22 cm −1 (in VPPE-AuNPs), specifies the N-H bending and bonding of primary amine [70]. A similar peak at 1635 cm −1 was also reported by Aina et al [71] when studying the synthesis of silver nanoparticles using papaya seed aqueous extract. The presence of primary amines signifying the protein content in papaya peels further evidenced that protein in the fruit's peel could have acted as a capping and stabilizing agent in the biosynthesis of VPPE-AuNPs [72,73].…”
Section: Vppe-aunp Manufacture and Analysissupporting
confidence: 79%
“…Carica papaya, known as papaya, papaw, or pawpaw, is a flowering and dicotyledonous plant classified as Violales order, Caricaceae family, Carica L. genus, and papaya species (papaya informally) [31]. Papaya trees are mostly cultivated in tropical and subtropical regions and are fast-growing and semi-woody with a lifespan of approximately 5-10 years [32].…”
Section: Introductionmentioning
confidence: 99%
“…Papaya trees are mostly cultivated in tropical and subtropical regions and are fast-growing and semi-woody with a lifespan of approximately 5-10 years [32]. Papaya fruits are melon-like, with green skin that turns yellow or orange when ripe and reportedly contain >1000 seeds [31]. Papaya tree parts could be a good candidate for the phytofabrication of AgNPs given their phytochemicals [30].…”
Section: Introductionmentioning
confidence: 99%